Prevalence of Human Papillomavirus, Chlamydia trachomatis, and Neisseria gonorrhoeae in Commercial Sex Workers in Japan - Kazuhisa Ishi; Fujihiko Suzuki; Akira Saito; Takeyoshi Kubota (Hindawi Limited, 2000)
Objective: We used the hybrid capture assays to investigate the prevalence of human papillomavirus (HPV), Chlamydia trachomatis and Neisseria gonorrhoeae among commercial sex workers in Tokyo.